Optimization of the Right Brain in Memorizing Al-Qur'an Juz 30 through the Tilawati Method at SD Islam Cendekia Assalam Bangilan Tuban - Zulfatun Anisah; Adhiesta Kurnia Fikri; Siti Effi Nur Ummahi (Universitas Muhammadiyah Sidoarjo, 2020)
Al-Qur'an memorization juz 30 needs to be supported by the right functional suitability of the brain and the use of appropriate and appropriate methods. So far, in Bangilan and other nearby districts, there is only one school that has a memorization juz 30 programs. Also, to reduce children's dependence on gadgets, children can be preoccupied with activities that are by their psychological and physical development, namely in the form of schedules or daily schedules. Children are filled with activities that are useful for themselves, now and for later days. This research uses a descriptive qualitative method. Researchers obtained data sources in the form of primary data and secondary data. Preliminary data were obtained from interviews, observations, and documentation conducted by researchers at the Islamic Scholar Assalam Elementary School. Meanwhile, secondary data obtained from library materials in schools include school vision and mission, teacher data, student data, and learning methods applied in schools. The results showed 9 of 39 students were able to memorize juz 30 faster. Only in one year, so starting from class 2, 9 students can continue memorization starting juz 1. As for the 30 other students, continue to memorize until completing juz 30. SD Islam Cendekia Assalam Bangilan chooses to use the method of tilawati in optimizing the right brain function. Long-term memory through music and art can help students more quickly remember and recite verses in Surah juz 30.